Promise me [compact disc, unabridged] - Coben, Harlan, 1962- (Coben, Harlan, 1962- Myron Bolitar novel., 2006)
As the school year winds down, Myron Bolitar is determined to help keep his friends<U+2019> children safe from the dangers of drinking and driving. So he makes two neighborhood girls promise him that if they are ever in a bind but are afraid to call their parents, they must call him. Several nights later, the call comes at two a.m. The next day, a girl is missing and Myron is the last person who saw her. Racing to find her before she<U+2019>s gone forever, Myron must outrun his own troubled past and decide once and for all who he is and what he will stand up for...